THE TRANSLATION OF ARABIC RELIGIOUS – CULTURAL COLLOCATIONS IN LITERARY TEXTS INTO ENGLISH: AN APPLICATION OF DOMESTICATION AND FOREIGNIZATION TRANSLATION STRATEGIES - Adham Mousa Obeidat; Tengku Sepora Tengku Mahadi (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
Since the goal of translation is to bridge the gap between two cultures, translators need to pay attention to literary works. Here lies the importance of good translation to convey cultural messages. The mistranslation of cultural concepts in a literary text may cause misunderstanding of this culture by the TL readers. Therefore, to produce a well- translated literary work, translators need to investigate the expressions that relates to culture such as religious beliefs. The vital role of cultural collocations in a language requires translators to apply effective translation strategies. Domestication and foreignization are two important strategies in translating cultural collocations in a literary text. The authors of this study have applied these strategies to investigate whether religious – cultural collocations in a literary text are domesticated or foreignized. The sentences that have religious – cultural collocations are chosen from an Arabic novel. The collocations are analyzed along with two versions of translation, then the English translations are compared. As a result of discussion, the two translators tend to apply the domestication strategy more frequently. It is found that since religious – cultural collocations are difficult to be understood by the target language readers, the translators tend to reduce their strangeness and domesticate them.